Packed bed reactor for degradation of simulated cyanide-containing wastewater - Kumar, Virender (3 Biotech, 2014)
The discharge of cyanide-containing effluents into the environment contaminates water bodies and soil. Effective methods of treatment which can detoxify cyanide are the need of the hour. The aim of the present study is to develop a bioreactor for complete degradation of cyanide using immobilized cells of Serratia marcescens RL2b. Alginate-entrapped cells of S. marcescens RL2b were used for complete degradation of cyanide in a packed bed reactor (PBR). Cells grown in minimal salt medium (pH 6.0) were harvested after 20 h and exhibited 0.4 U mg(−1) dcw activity and 99 % cyanide degradation in 10 h. These resting cells were entrapped using 3 % alginate beads and packed in a column reactor (20 × 1.7 cm). Simulated cyanide (12 mmol l(−1))-containing wastewater was loaded and fractions were collected after different time intervals at various flow rates. Complete degradation of 12 m mmol l(−1) (780 mg l(−1)) cyanide in 10 h was observed at a flow rate of 1.5 ml h(−1). The degradation of cyanide in PBR showed direct dependence on retention time. The retention time of cyanide in the reactor was 9.27 h. The PBR can degrade 1.2 g of cyanide completely in 1 day.